Evaluation of adipokine levels in obese women with periodontitis: A cohort study - Alkan, Begüm; Güzeldemir Akçakanat, Esra (Mosher and Linder, Inc, 2021)
Purpose: To evaluate the inflammation-related adipokine levels in the body fluids of obese female participants with and without periodontitis using healthy participants as a control group. Methods: A cohort design study was carried out at Kocaeli University between December 2014 and June 2015. The study sample comprised 25 obese female participants with periodontitis (Group 1), 31 obese female participants without periodontitis (Group 2), and 15 lean female participants with healthy periodontium (Group 3), from whom body mass index, clinical periodontal parameters were measured, and serum, saliva, and gingival crevicular fluid (GCF) samples were collected. The three groups' periodontal parameters and adipokine levels were evaluated and compared, and the primary outcome was the difference in local and systemic adipokine levels between the study groups. Results: In the participants' serum samples, tumor necrosis factor-alpha (TNF-alpha) and leptin levels were lower, whereas adiponectin levels were significantly higher in Group 3 than in the obese groups (P<0.05). In the participants' saliva samples, interleukin-1 beta, TNF-alpha, and resistin levels were lowest in Group 3, but adiponectin was lowest in Group 2 (P< 0.05). In the participants' GCF samples, interleukin-113, resistin, and adiponectin levels were higher in Group 1 (P< 0.05). This study showed that the amounts of the adipokines could differ in serum, saliva, and GCF samples from obese female participants with and without periodontitis and from lean female participants with healthy periodontium. CLINICAL SIGNIFICANCE: Periodontal diseases in different severities can affect overall health by altering the amounts of adipokines (IL-1 beta, TNF-alpha, leptin, resistin, and adiponectin) in serum, saliva, and GCF of obese female patients. Clinicians should be aware that periodontal disease can alter inflammatory adipokine levels and may affect other treatment outcomes in obese female patients.
Keywords: Obese Women; Adipokine Levels; Periodontitis